Knowledge, attitude and practice. Of guardians and adult patients towards upper respiratory tract infection at klinik perubatan masy araka t (kpm), husm - Yahaya , Zaiton (2001)
Aim: The study was to detennine the basic knowledge, attitude and practice of adult patients and guardians who came to Klinik Perubatan Masyarakat for treatment of Upper respiratory tract infections. Method: This was a cross sectional study involving 369 respondents with 190 guardians and 179 adults who came to KPM within the period of 4 months between 1 st August and 31st, December, 2000 for treatment of URTI. Once diagnosed to have URTI the respondents were given self-administered questionnaires. The respondents will answer the questionnaires if they were 18 years old or above and for the children who were below 18 years old, their guardians or caretakers will answer the questionnaires. Results: The results showed, significant difference between the two groups with respect to the age of the respondents, marital status, educational status and income and their state of employment. Mean age for the guardians was 35 ± 7.53 years and 29.5 ± 10.36 years for adult patients. Sixty-four percent of children who were brought to KPM for URTI were aged less than 5 years old. The average income of the guardians was RM 1242 ± 732 and RM 957.57 ± 639.26 for the adult patients. Two thirds of the respondents had completed education up to secondary level.